Crystallization and preliminary X‐ray diffraction analysis of D53H mutant Escherichia coli cAMP receptor protein. Issue 12 (1st December 2013) - Huang, Jing; Wu, Tong; Guo, Zheng; Lou, Tiantian; Yu, Shaoning; Gong, Weimin; Ji, Chaoneng
<x xml:space="preserve">Abstract</x> The Escherichia coli cyclic AMP receptor protein (CRP) is a prokaryotic global transcription activator protein that controls the expression of many different genes. Wild‐type CRP can bind to special DNA sequences in the presence of cAMP. The substitution of Asp53 by His results in the CRP* phenotype, which does not require exogenous cAMP. In the present study, the D53H CRP mutant was overexpressed, purified and crystallized. cAMP‐free D53H CRP crystals were obtained and diffracted to a resolution of 2.9 Å. Based on the systematic absences of the crystals, the space group is likely to be P212121, with unit‐cell parameters a = 76.66, b = 152.14, c = 176.11 Å. The asymmetric unit was confirmed to contain four protein dimers, with a Matthews coefficient of 2.71 Å3 Da−1 and a solvent content of 54.68%.